A Case Study Of Singapore Telecom Mobile Pte Limited - Goh, Chee Wei (2005)
SingTel is a leading Asia Pacific telecommunication company with substantial international operations in east Asia, South Asia and Australia. Singapore Telecom Mobile Pte Limited is a subsidiary company of SingTel Group and the subsidiary provide mobile data services and application to both home and business users.